P176 Update on UK outcomes in twin pregnancies with complete hydatidiform mole and normal co-twin: a retrospective national cohort study in 153 new cases. (1st November 2019) - Russell, JC; Niemann, I; Sebire, NJ; Fisher, RA; Short, D; Everard, J; Wells, M; Savage, PM; Sarwar, N; Hancock, BW; Tidy, J; Seckl, MJ
Abstract : Introduction/Background: Uncertainty remains regarding management of twin pregnancies comprising complete hydatidiform mole (CHM) and healthy co-twin. In 1998, we reported that continuing such pregnancies results in a 38% chance of a healthy baby, no maternal deaths or increased risk of malignancy requiring chemotherapy. However, other studies suggest a higher risk of malignancy and maternal mortality if such pregnancies are not terminated. Here, we re-examine this controversial issue in a new, larger national cohort. Methodology: The UK hydatidiform mole databases were screened to identify all twin pregnancies with central pathology review confirming CHM and normal co-twin between 1998 and 2018. Data on rates of termination, spontaneous miscarriage, pregnancy complications, successful deliveries and need for chemotherapy were collected. Results: 153 new patients had a confirmed CHM and healthy co-twin. Fifty electively terminated their pregnancy before 14 weeks. 103 continued beyond 14 weeks but 28 subsequently electively terminated, leaving 75 patients who continued their pregnancy. Their outcomes included: 11 terminations <24 weeks for complications (4 pre-eclampsia, 1 intrauterine infection and 6 bleeding); 5 stillbirths (27–35 weeks), 2 neonatal deaths and 19 spontaneous abortions/miscarriages. Strikingly, 51% (38/75) delivered a surviving baby at a median gestational age of 30 weeks (range 24–40 weeks). Malignant change requiring chemotherapy was not significantly different whether pregnancies were terminated within 14 weeks (12/56, 21.4%), continued into the second (12/58, 20.7%) or third trimester (7/39, 17.9%) (p=0.40). However, malignancy risk is higher in twin (20.3%) than singleton (16%) CHM pregnancies. Importantly, there were no maternal deaths. Conclusion: Although malignancy risk is slightly greater following CHM and healthy co-twin than in singleton molar pregnancies, the risk does not increase with progression of pregnancy beyond the first trimester. Early termination is not necessary, and the likelihood of a healthy baby appears to be greater than previously reported. Disclosure: MJS wishes to acknowledge support from the Imperial National Institute for Health Biomedical Research Centre and Cancer Research UK Imperial Experimental Cancer Medicine Centre. NJS is partly supported by an NIHR Senior Investigator award. JCR has nothing to disclose. IN has nothing to disclose. RAF has nothing to disclose. DS has nothing to disclose. JE has nothing to disclose. MW has nothing to disclose. PMS has nothing to disclose. NS has nothing to disclose. BWH has nothing to disclose. JT has nothing to disclose.